SUSTRA LOWIS: STRENGTHENING TOURISM INDUSTRY TO REALIZE INDONESIA AS GLOBAL MARITIME AXIS - Pipin Nur Azizi (OISAA, 2018)
Indonesia is the world’s largest archipelago country and it has coastline stretching from Sabang toMerauke with more than 17.500 islands. As a maritime country, Indonesia has potential on marinetourism which can be a backbone of economy amid the global economic turmoil. However, theperformance of Indonesian tourism has not shown satisfactory results if viewed from the data offoreign tourist visits which is left behind with neighboring countries. The implementation ofSUSTRA LOWIS (Sustainable Tourism Strategy Based on Local Wisdom) is expected to increase therole of Indonesia's marine tourism sector to the economy by improving the quality of tourismmanagement and human resources. Development of tourism must involve the role of society, butgovernment is less concerned about it.The purpose of this paper is to create innovations to enhancethe role of marine tourism industry to Indonesian economy, explaining that Indonesia has tremendousmaritime potential and can be utilized for the collective interest and provide an overview to thegovernment on programs that can be implemented for the marine tourism industry. This type ofresearch is descriptive analysis. The study aims to analyze and describe the implementation ofSUSTRA LOWIS as an effort to realize Indonesia as the world’s maritime axis. Data were collectedthrough observation and literature studies. The research concluded that SUSTRA LOWIS(Sustainable Tourism Strategy Based on Local Wisdom) has five main sectors for the development ofmarine tourism those are, Tourism Management Sector (TMS), Tourism Training Sector (TTS),Business Improvement Sector (BIS), Technology Based Tourism Sector (TBTS), and MaritimeEducation Sector (MES). These five sectors have programs that can support the development ofmarine tourism thoroughly and sustainably to realize Indonesia as the world’s maritime axis.